Newborn and infant discrimination: revisiting footprints. Issue 1 (2nd January 2019) - Kotzerke, J.; Davis, S. A.; Hayes, R.; Horadam, K. J.
ABSTRACT : Formal registration of newborns and infants is a necessity to secure their rights for health care or education and to support law enforcement agencies in the fight against the trafficking of children or their illegal adoption. Ideally, all these requirements can be met using a newborn and infant biometric. Difficulties arise due to the small size and fragility of the infants' physical structures and the effects of rapid physical growth. We review the literature for suitable biometrics and investigate the footprint; asking (a) if there is a time frame shortly after birth when the friction ridge skin pattern of a newborn can be reliably captured; and (b) if the footprint crease pattern is a suitable newborn and infant biometric. For (a), we were unable to confirm the existence of such a time frame. For (b), we performed automatic verification experiments on a small test set of 20 pairs of crease patterns, and then a larger test set, achieving EERs of 22.22% and 46.39%, respectively. The comparison of two dizygotic twins did not show any noteworthy performance difference. Based on these results we do not recommend the foot crease pattern as a newborn or infant biometric for automatic verification.